1992
DOI: 10.1126/science.1388288
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Activation of a Cyclin E-cdk2 Complex During the G 1 Phase of the Human Cell Cycle

Abstract: Human cyclin E, originally identified on the basis of its ability to function as a G1 cyclin in budding yeast, associated with a cell cycle-regulated protein kinase in human cells. The cyclin E-associated kinase activity peaked during G1, before the appearance of cyclin A, and was diminished during exit from the cell cycle after differentiation or serum withdrawal. The major cyclin E-associated kinase in human cells was Cdk2 (cyclin-dependent kinase 2). The abundance of the cyclin E protein and the cyclin E-Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
597
2
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 982 publications
(639 citation statements)
references
References 17 publications
33
597
2
7
Order By: Relevance
“…As shown in Figure 3a, TIMP-1 overexpression lead to a significant decrease in the cyclin D 1 level, a G 1 cyclin critical for cell cycle entry and G 1 progression (Motokura and Arnold, 1993;Hatakeyama et al, 1994), whereas it induced the level of cyclin E1 expression, a late G 1 cyclin critical for the cell cycle progression into the S phase Hinds et al, 1992;Koff et al, 1992). Since kinase activities of cyclin complexes are regulated by CDKIs, we also examined the effects of TIMP-1 overexpression on CDKI expression.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3a, TIMP-1 overexpression lead to a significant decrease in the cyclin D 1 level, a G 1 cyclin critical for cell cycle entry and G 1 progression (Motokura and Arnold, 1993;Hatakeyama et al, 1994), whereas it induced the level of cyclin E1 expression, a late G 1 cyclin critical for the cell cycle progression into the S phase Hinds et al, 1992;Koff et al, 1992). Since kinase activities of cyclin complexes are regulated by CDKIs, we also examined the effects of TIMP-1 overexpression on CDKI expression.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 Miller et al 45 reported that miR-221/222 expressions were upregulated in endocrine therapy-resistant luminaltype breast cancer cells. MiR-221/222 are negative regulators of p27 kip1 , a cell cycle inhibitor and tumor suppressor, [46][47][48][49][50] and upregulated expressions of these miRNAs and significant reductions in p27 kip1 levels have been reported in tamoxifen-resistant breast cancer cells; therefore, miR-221/222 might regulate tamoxifen sensitivity via the direct targeting of p27 kip1 . 51,52 Pichiorri et al 53 found that miR-221/222 expressions were modulated by nucleolin at the post-transcriptional level.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…Inactivation of pRb repression of E2F results in the transcription of Cyclin E, and Cyclin A, as well as E2F itself prior to the G1/S transition stage (Woo and Poon, 2003). At the onset of S phase, Cdk2 (Cdc28 in yeast) is activated by expressed Cyclin E subunits, which then continues the phosphorylation of pRb (Koff et al, 1991;Koff et al, 1992). Accumulating Cyclin A generated from the pRb/E2F…”
Section: A Brief Description Of Cell Cycle Progression From G1 and S mentioning
confidence: 99%